Modeling the evolution of a primitive supply chain. - Tay, Darrell Jiajie. (2012)
Recent works by Li et al. (2010), Holweg and Pil (2007) have recognized Supply Networks (SNs) as Complex Adaptive Systems (CAS). In this project, we study the evolution of a primitive supply chain using agent based computer simulations with CAS characteristics. By allowing the system to evolve in a way postulated by the Reformulated 2nd Law of Thermodynamics (Schneider and Kay, 1994), we inspected the end state energy of the primitive supply chain for different types of evolution. We find that contrary to mature supply chains, primitive supply chains is less affected by information sharing due to a high level of symmetric information shared. However, primitive SNs can still enhance their end state total energy significantly through self-organization and through increasing the levels of structure and hierarchy.